Eating Bhorthas in America: Exploring Dietary Changes upon Migration Among Bangladeshi Muslims Women in New York City (P04-123-19) - Shukla, Prova (Curr Dev Nutr, 2019)
OBJECTIVES: The United States is experiencing an increased influx of Bangladeshi and Bengali immigrants, yet there is limited research on how migration may affect the traditional diet in this population. Addressing this research need, the present study aimed to: (1) Examine the dietary changes upon migration among Bangladeshi women in New York City (NYC), and (2) Explore the influence of religion (Islam) on the dietary acculturation process. METHODS: Cross-sectional qualitative study, using semi-structured interviews with 18 Bangladeshi-born, Muslim women, who immigrated to the US within the last 15 years. Interview transcripts were analyzed iteratively using Dedoose to organize and compare themes emerging from the interview. RESULTS: The women reported having access to traditional ingredients in NYC, given the expansion of South Asian stores. Drivers for dietary change included trying new foods as part of celebrating American holidays, learning about new foods through their children, and trying new recipes for American and other ethnic foods found through social media. Following Islamic diet laws prevented the women from consumption of pork products, and led them to modify dishes served during American holidays (i.e., Thanksgiving, Memorial Day, Fourth of July, and Labor Day). Changes were also reported in views regarding the healthfulness of Bengali cuisine after migration. These changes included the switch to brown rice instead of white rice, grilling meat rather than frying, and portion control. CONCLUSIONS: This study contributes to understanding of the dietary acculturation process in Bangladeshi- American population, including the influence of religion in the process. The results show that immigrants seek to keep their identities and that food is one of the main ways to keep their memories of their homelands. These findings can be applied to future interventions targeting the growing South Asian immigrant population in the US. FUNDING SOURCES: CUNY-Brooklyn College.